The philosophical perspective of the problem of time in contemporary philosophical thought - Jeru, Mohammed Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
Time is one of the humanistic philosophical concepts, especially with regard to religious beliefs and constants that people have taken care of since ancient times, especially among the Greeks. The concept of time has become of historical value, especially among contemporary philosophers, and problems of philosophy begin with time such as temporal and non-existence and other philosophical problems.